Quercetin Inhibits Biofilm Formation by Decreasing the Production of EPS and Altering the Composition of EPS in Staphylococcus epidermidis - Mu, Yongqi; Zeng, Hong; Chen, Wei (Frontiers in Microbiology, 2021)
Staphylococcus epidermidis is an opportunistic pathogen, and its biofilm formation ability is an important virulent factor. Quercetin, a typical flavonoid ubiquitously used in dietary supplementation, is known for its antioxidant property, but its anti-biofilm activity against S. epidermidis remains unknown. In this study, the anti-biofilm activity of quercetin was investigated using S. epidermidis ATCC35984, a strong biofilm-positive strain. An attempt was made to disclose the mechanisms of the anti-biofilm activity of quercetin. S. epidermidis exhibited a less cell surface hydrophobicity after quercetin treatment. Also, quercetin effectively inhibited S. epidermidis cells from adhering to the glass slides. Quercetin downregulated the intercellular adhesion (ica) locus and then polysaccharide intercellular adhesin (PIA) production was reduced. Therefore, S. epidermidis cells became less hydrophobic, which supported quercetin’s anti-biofilm effect. Our study suggests that quercetin from plants be given further attention as a potential anti-biofilm agent against the biofilm formation of S. epidermidis, even biofilm infections of other bacteria.